Magyar diákok a külföldi tanulásról : empirikus vizsgálatok megállapításai - Rédei, Mária (Közép-Európai Közlemények, 2008)
The article deals with the roll of Hungary in international foreign study. Hungary became a host and sending country, by 15.000 incoming and 10-8.000 outgoing students. Our survey was carried out among the 300 students in 2008. The second halt of paper point out the structure, motivation, and the value of answers. It strengthens the importance of family background. 5-6% of students never been abroad. Most of them are the first from the family, who spend longer period in a foreign country. 2,5% of student were not Hungarians, they arrived from surrounding countries. The geographical choice of staying among the girls was more diverted. High proportion mentioned to stay longer period in abroad.